(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
In the modern educational landscape, traditional teaching methods often struggle to engage students, especially in foreign language learning. Gamification, which integrates game-like elements into education, has emerged as an innovative approach to enhance motivation, engagement, and effectiveness in language acquisition. This paper explores the benefits of gamification in foreign language classes, including increased motivation through point systems and rewards, the promotion of active learning through interactive games, and the provision of immediate feedback. Additionally, gamification fosters inclusivity, encourages competition, and offers real-world language application, ultimately nurturing a love for lifelong learning